Ministry of Trade and Industry Decree Of The Minister of Trade And Industry And Minister Of Finance No. 772 of the Year 2010 = وزارة التجارة والصناعة قرار وزير التجارة والصناعة ووزير المالية رقم 772 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.